General practitioners' attitudes and behaviors toward HPV vaccination: A French national survey. Issue 6 (3rd February 2016) - Collange, Fanny; Fressard, Lisa; Pulcini, Céline; Sebbah, Rémy; Peretti-Watel, Patrick; Verger, Pierre
Highlights: We assessed French GPs' attitudes and behaviors about HPV vaccination. HPV vaccine hesitancy is fairly prevalent among GPs. Perception of the vaccine risk-benefit balance is the strongest determinant of this behavior. Abstract: Objective: General practitioners (GPs) play a crucial role in human papillomavirus (HPV) vaccine acceptance in France. We sought to study: (1) GPs' perceptions of its risks and efficacy and their recommendation behavior; (2) the relative importance of factors associated with the frequency of their recommendations. Methods: Cross-sectional observational study in 2014 nested in a national panel of 1712 randomly selected GPs in private practice in France (response rate: 92.4%). We used model averaging to analyze the associations of self-reported frequency of GPs' HPV vaccine recommendations with their perception of its risk-benefit balance and their opinions about the utility of vaccines in general. Results: Overall, 72% of participants reported frequently recommending HPV vaccination; 60% considered that not enough is known about its risks. The model averaging showed that the factors most associated with infrequent recommendation of this vaccine by GPs were: unfavorable perceptions of its risk-benefit balance (OR = 0.13; 95%CI = 0.09–0.21; partial R 2 = 0.10), a decision not to vaccinate one's own daughter(s) with this vaccine (OR = 0.13; 95%CI = 0.07–0.24; partial R 2 = 0.05), and doubts about vaccine utility in general (OR = 0.78; 95%CI = 0.71–0.86; partial R 2 = 0.03). Conclusion: Although nearly three-quarters of French GPs frequently recommended the HPV vaccine, our findings indicate that a substantial percentage of them are hesitant about it. Doubts about its risks and efficacy strongly influence their recommendation behavior. More research is warranted to help design and evaluate tailored tools and multicomponent intervention strategies to address physician's hesitancy about this vaccine.